Context and Implications Document: Methodological diversity as an asset for transition-focused higher education research with students from refugee backgrounds - Baker, S.; Irwin, E.; Taiwo, M.; Singh, S.; Gower, Shelley; Dantas, Jaya (2019)
This guide accompanies the following article: Baker, S., Irwin, E., Taiwo, M., Singh, S., Gower, S. & Dantas, J. Methodological diversity as an asset for transition‐focused higher education research with students from refugee backgrounds, Review of Education, https://doi.org/10.1002/rev3.3133.